Challenges and responses for the convergence of people living in deep poverty in Hungary - Siposné Sinóros-Szabó, Laura (Acta Agraria Debreceniensis, 2014)
The accompanying phenomenon of the ongoing economic crisisis the deepening and fixation of awidely reaching social crisis. The concept o fdeep poverty has become generally known in recent years and has now become inevitable the convergence of the most disadvantaged at EU, governmental,regional and local levels. Besides government and othe rprograms a lot of research and studies serve reintegration. Among convergence tools education and training play prominent roles, which besides the acquisition o fpractical knowledge, place special emphasis on the development of a convergence helping environment and culture, the creation of a "convergenceculture".